Hysterectomy by transvaginal natural orifice transluminal endoscopic surgery: An Italian initial experience - Interdonato, Maria Lieta; Scollo, Paolo; Bignardi, Tommaso; Massimello, Francesca; Ferrara, Martina; Donatiello, Gianluca; Caretto, Marta; Mannella, Paolo; Pecorino, Basilio; Meroni, Mario Giuseppe; Simoncini, Tommaso (Frontiers in Medicine, 2022)
Background: The aim of this study is to evaluate the initial feasibility, safety, and outcomes of hysterectomy performed by transvaginal Natural Orifice Transluminal Endoscopic Surgery (vNOTES) at three institutions in Italy. Materials and methods: All women who underwent vNOTES hysterectomy +/- salpingo-oophorectomy at three tertiary referral medical centers between July 2019 – April 2021, were included in a retrospective analysis. All vNOTESs were performed with the use of Alexis® and Vpath Gel paths® (Applied Medical). Perioperative data were extracted from patient records. Patient satisfaction and dyspareunia were prospectively inquired at 60 days and 6-months. Results: Forty-six patients underwent vNOTES in the study period. Indications for surgery included myomas±metrorrhagia (52.2%), H-Sil/ In situ cervical cancer (10.7%), adenomyosis±metrorrhagia (8.7%), BRCA 1-2 mutations (6.5%), endometrial hyperplasia (6.5%), ovarian cyst+history of breast cancer (6.5%), metrorrhagia (6.5%), hydatiform mole (2.2%). Mean operation time was 91,1 (±32,6) minutes. Mean hemoglobin drop was 1.2 (±0.8). Mean visual analog scale at 24 h for postoperative pain was 3.3 (±1.8). Secondary to our limited experience with the surgical technique, we favor discharge only from day 1. Mean length of hospital stay was 2 (±1.4) days. Two conversions to conventional laparoscopy were reported (4.3%), due to an obliterated pouch of Douglas and a preoperative complication. Two postoperative complications were reported (4.3%). Overall, our data on peri- and post-operative outcomes are similar to those already published for vNOTES. Conclusion: Our experience suggests that introducing vNOTES as an alternative to conventional surgery is feasible and may offer some advantages in selected women.